Role of the Female Community Health Volunteers (FCHVs) for Continued Improvement in Primary Healthcare in Nepal - Shahi, Prakash; Tamang, Pasang `; Bhatta, Surya; Rawal, Lal (Europasian Journal of Medical Sciences, 2021)
Community health workers (CHWs) have played a vital role in improving primary healthcare services in different parts of the world, in particular, for those services related to the prevention and control of communicable diseases, immunization services, reproductive health, maternal and child health, HIV/AIDS prevention and care and nutrition promotion. The Female Community Health Volunteers (FCHVs) program, which was introduced in 1988 in Nepal, has now reached over 51,000 FCHVs. They are key community level CHWs in Nepal and have contributed significantly in achieving several health and related outcomes and meeting several Millennium Development Goals. In such, there is also a potential and needs for engaging them to prevent and control emerging health challenges such as non-communicable diseases prevention and control and re-emerging health issues. Their effective involvement to ongoing health programs would be critical to achieving Sustainable Development Goals, agenda in particular “SDG 3 – Health and Wellbeing” by 2030. DOI: https://doi.org/10.46405/ejms.v3i2.364